PENGEMBANGAN KAMUS NAMA ILMIAH HEWAN JENIS MAMALIA PADA MATERI VERTEBRATA UNTUK SISWA KELAS X SMA - Ranti Juliana; Eko Wulandari; Arista Ratih (BIOCOLONY, 2022)
This research is motivated by the use of media in the Biology learning process at school which is not optimal. In biology learning there are terms in Latin that are used in learning. The existence of these terms makes students feel difficult in interpreting. Therefore, researchers developed a dictionary of scientific names of mammals as a support for students' biological learning at school. This study aims to describe the process of developing a dictionary of scientific names for mammals at SMA Negeri 11 Merangin and to produce a valid and practical dictionary of scientific names for class X SMA Negeri 11 Merangin. This research is a development research that uses the stages of the 4-D model which includes the define, design, and develop stages. In this study there were 6 validators with the research subjects consisting of 25 class X students of SMA Negeri 11 Merangin. This research instrument uses a validity questionnaire and a practicality questionnaire. Research data validation results and practicality of scientific name dictionaries, then analyzed with descriptive analysis. Based on the results of the study, it was obtained that the validity of the questionnaire data was 86% in terms of content feasibility, 89% in terms of language, 88% in terms of presentation, and 91% in terms of graphics, with an overall average percentage of questionnaire validity results of 88.5% (very valid). The dictionary of scientific names produced also obtained results in terms of ease of use of 3.6 stated to be very practical, in terms of learning time of 3.7 stated to be very practical, in terms of attractiveness of 3.7 stated to be very practical. So that the average product practicality was stated to be very practical by the teacher with an average value obtained, namely 3.6, the result of the teacher's assessment. So it can be concluded that the resulting dictionary of mammal animal scientific names is valid and practical.